A Relational Study on Individual Values: An Example from Turkey - Demirel, Gönül; Göl, Buket (Archives of Business Research, 2018)
A major concern for institutions especially over the past few decades has been the recognition of individual values as among the sources and determinants of intention to quit among employees. In this respect, Schwartz has come up with a general value system based on differences across cultures producing variations in personalities which in turn affect peoples’ behaviors through their actions. Thus, according to Schwartz, universal and culture-specific aspects of values show variation in personalities that in turn dictate the expected employee behavior permitting in this way to form a compatible work environment. In this study, the Schwartz value system is empirically tested to determine its effects on intention to quit for employees working in a software company in Istanbul, Turkey. Sources and determinants of intention to quit due other than to Schwartz individual values have been quite extensively studied in the literature. In the literature, affective commitment, perceived organizational support, and differences in wage expectations have been shown empirically significant as among the determinants of intention to quit. This study aims to determine and test empirically the effects of individual values and affective commitment only on intention to quit. In doing so, the study also aims to test empirically the effects, if any, of Schwartz individual values on affective commitment and affective commitment on intention to quit.